Karakteristik Pasien Tuberkulosis Paru Dengan HIV di Rumah Sakit Umum Daerah Dr Harjono Ponorogo Periode Januari 2018 - Desember 2022 - Anindya Zalfaa Kusuma Dewi; Ronald Pratama A.; Dody Taruna; Irmawati M. Dikman; Soedarsono Soedarsono; Yelvi Levani (Universitas Muhammadiyah Surabaya, 2024)
Tuberculosis (TB) is the most common opportunistic infection in people living with HIV/AIDS in Indonesia, and HIV infection promotes Mycobacterium tuberculosis infection. In ODHIV, the probability of contracting TB is 10% per year. According to the Indonesian Ministry of Health, East Java is in second place with 71,909 cases and has the second highest number of AIDS patients and 824,000 TB cases in Indonesia. This study aims to determine the characteristics of pulmonary tuberculosis patients with HIV at DR Harjono Ponorogo Hospital for the period January 2018 - December 2022. This study applied descriptive research methodology with quantitative techniques with secondary data from medical records of pulmonary TB patients with HIV at Dr. Harjono Ponorogo Hospital for the period January 2018 - December 2022. The results showed a total sample of 130 medical records, there were several characteristics of TB patients with HIV, namely the highest age group of 30-39 years by 29.2%, more in male gender 73%. More patients had last high school education 38.5%, more treatment duration in patients who did for 9 months 61.5% and the results showed more patients with poor prognosis 56%. In conclusion, the characteristics of TB patients with HIV with the highest group at the age of 3-39 years, having male gender, more high school education, with more treatment duration of 9 months, and the results showed a poor prognosis.